2007
DOI: 10.1007/s00122-007-0601-6
|View full text |Cite
|
Sign up to set email alerts
|

Association mapping of Stagonospora nodorum blotch resistance in modern European winter wheat varieties

Abstract: Association mapping in populations relevant for wheat breeding has a large potential for validating and fine-mapping QTLs identified in F2- or DH (double haploid)-derived populations. In this study, associations between markers in the region of QSng.sfr-3BS, a major QTL for resistance to Stagonospora nodorum glume blotch (SNG), and SNG resistance were investigated by linkage and association analyses. After increasing marker density in 240 F(5:7) recombinant inbred lines (RILs), QSng.sfr-3BS explained 43% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 45 publications
5
81
0
4
Order By: Relevance
“…The number of genotypes used is not large enough for a new study on association mapping where QTLs have to be mapped. However, the number is adequate (considering also our limitations of handling large population) for validating QTLs already reported as in our study and also several other previous such studies on wheat (44 genotypes, Tommasini et al 2007) soybean (44 genotypes, Singh et al 2008) and rice (40 genotypes, Vannirajan et al 2012). Moreover, clear population structure was observed using 48 genotypes (including four sets of elite × wild derived introgression lines, landraces and mutants) thus permitting genome-wide association mapping.…”
Section: Discussionsupporting
confidence: 52%
“…The number of genotypes used is not large enough for a new study on association mapping where QTLs have to be mapped. However, the number is adequate (considering also our limitations of handling large population) for validating QTLs already reported as in our study and also several other previous such studies on wheat (44 genotypes, Tommasini et al 2007) soybean (44 genotypes, Singh et al 2008) and rice (40 genotypes, Vannirajan et al 2012). Moreover, clear population structure was observed using 48 genotypes (including four sets of elite × wild derived introgression lines, landraces and mutants) thus permitting genome-wide association mapping.…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, we identified 24 QTL with −log 10 (P value) >3.0 for resistance to the disease caused by the five isolates. Tommasini et al (2007) reported the detection of a major SNB resistance QTL on 3BS using an association mapping approach with only 44 European winter wheat cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been done to map resistance to the two diseases using the association mapping approach Gurung et al 2011;Kollers et al 2014;Patel et al 2013;Tommasini et al 2007). Because different marker types (simple sequence repeat or diversity arrays technology) have been used, it is difficult to compare Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…By analysing a collection of cultivars instead of a segregating population it is possible to obtain a much higher marker resolution as was demonstrated by the study of Tommasini et al (2007), who observed a 390-fold higher marker resolution with a collection of 44 winter wheat cultivars compared to a RIL population.…”
Section: Variety Analysismentioning
confidence: 99%